The impact of infrastructure development on economic growth in South Africa - Managa, Fhatuwani (My University, 2019)
The research methodology followed used semi-structured interviews to gather data on the impact of infrastructure on economic growth in South Africa. Semi-structured interviews are suitable for conducting small scale research and allows the researcher to exercise some flexibility during the interview process. According to Drever (1995) for small scale research, semi-structured interviews is the most commonly used method. The main objective of semistructured interviews is to give the interviewee or interviewees a platform to voice their own understanding and knowledge on the subject matter (Longhurst, 2003; Scheibelhofer, 2008). Semi-structured interviews unlike structured interviews do not follow a predetermined and standardised set of questions. Eight people were interviewed whose experience range from microeconomics and macroeconomics analyst, infrastructure procurement, consumer markets advisory specialising in power and energy, debt financing of infrastructure development, former Ambassador of South Africa to some African countries as well as other parts of the world, and investment banking. The interviewed candidates between them have more than 30 years working experience. On average each interview took 30 to 40 minutes long. Infrastructure is vital in enabling competition and allows you to compete in the global market. Infrastructure development is seen as a catalyst, and an enabler for potential economic growth. The interviewee’s identified that infrastructure gaps prevent countries such as South Africa from realising their full potential. Infrastructure gap introduces inefficiencies into the daily activities of consumers and business which can be costly. Majority of the participants are of the view that growth is linked to connectedness and network of a country. Should a country want to trade with other countries, it requires a certain level connectedness which is achieved through road networks, railway lines and telecommunication among other things. It is this network and connectedness that is currently lacking with South Africa and the rest of Africa. The analyses of the data gathered shows that infrastructure development is a key enabler for economic growth. South Africa should focus on, one, closing the Infrastructure gaps which hinder and slow economic growth, two, increase railway networks, and three expand harbours and ports which are critical for imports and exports. If these gaps are not closed, the cost burden will fall upon the consumers and businesses, and in turn, the economy. It was evident through the interviews with the participants that infrastructure development contributes to growing economies and will help countries sustain economic growth margins. What South Africa should also focus on increasing business confidence by reducing political instability, and tackling corruption by implementing robust judicial systems, governance and policies. It Protocol number: (WBS/BA313898/670) 6 is also important to hire people who are competent and who understand of how economy works practically and not just theoretically, so that they can make correct investment decision and lead the country in the right direction. This will help attract Foreign Direct investments as well as help local entities that are sitting on surplus cash invest in projects such as infrastructure development. When the participants were asked why infrastructure development is important, the participants responded by saying, if you look at the bulk of goods that we buy on a daily basis, they are transported by road, and that can be very expensive. Bulk goods need to be transported by railway to reduce time and cost of delivery. The cost of time and delivery impact on the pricing of the goods. So investing in infrastructure development such as rail can increase production and reduce cost of production at the same time. Increase in productive good in turn stimulate the economy. Input costs can either drive prices up or down depending on the quality and efficiency of supporting infrastructure development. A key finding, which is supported by the literature review, the more South Africa builds and invests in infrastructure development, the more efficient South Africa’s markets will become which will in turn drive operating costs and the cost goods or services down. This research paper focused on the impact of road, energy and telecommunications infrastructure development has on economic growth, the results show that these areas of infrastructure can lead to economic growth, if the right investment decisions are made. Infrastructure development can lastly be used as a mechanism to curb rising rate of youth unemployment. Keywords: Infrastructure development; Economic growth
MBA
Keywords: Infrastructure (Economics) -- South Africa. Economic development -- South Africa.